Modeling and Analysis of Percentage Depth Dose (PDD) and Dose Profile of X-Ray Beam Produced by Linac Device with Voltage Variation - Bilalodin Bilalodin; Farzand Abdullatif (Universitas Ahmad Dahlan, 2022)
The Percentage Depth Dose (PDD) and dose profile of X-Ray output from a LINAC therapy device have been modeled and analyzed. The research was conducted by simulation method through the use of Particle and Heavy Ion Transport code System (PHITS) program. The LINAC therapy device modeled in this work refers to the Siemens Primus LINAC therapy device, which is operated at 6 MV, 10 MV and 18 MV voltages. Determination of PDD was carried at a depth of 0-30 cm and dose profile at a depth of 0-20 cm in a water phantom, placed at 100 cm from the source, which is exposed to a radiation field area of 10Ã—10 cm2. Results from the modeling of the LINAC therapy device agrees with the actual X-ray apparatus and has produced Bremsstrahlung X-ray. It was found from the analysis of the PDD curve that the maximum doses are at the depth of 1.5 cm, 2.5 cm and 3.4 cm. The value of build up factor for each LINAC voltage agrees with the reference. Additionally, Â the results of the analysis of the doses profile suggest that the X-ray output has good degree of uniformity. The flatness of dose profile occurs at the depth of 20 cm with percentage value of flatness at 1.6 %, 1.9 % and 1.2 %. The flatness values are all less than 2%. The flatness values shows â‰¤ 2 % deviation from reference value, which is below the tolerance range required in a measurement.